Comparison of inner ear drug availability of combined treatment with systemic or local drug injections alone. (June 2020) - Li, Yang; Kanzaki, Sho; Shibata, Shinsuke; Nakamura, Masaya; Ozaki, Masahiro; Okano, Hideyuki; Ogawa, Kaoru
Highlights: An in vivo imaging system is used to study the pharmacokinetics of combined therapy in the inner ear. Biological half-life and total photon counts increased after combined therapy. Combined therapy cannot strengthen the peak photon of the drug in the inner ear. Abstract: Combination of systemic and local drug therapy has been proved more effective and safer for idiopathic sudden sensorineural hearing loss by some clinical trials, and there are few laboratory researches on its pharmacokinetic behaviors in the inner ear. In the present study, we use a new in vivo imaging system to compare the pharmacokinetics of combined therapy (CT), with intravenous (IV) or transtympanic (TT) injection alone in both ears of transgenic GFAP-Luc mice. Biological half-life, total photon counts and the area under the curve (AUC) value significantly increased after CT. However, adding IV to TT injection cannot strengthen the peak photon of the drug in the inner ear. In addition, when D-luciferin is injected to the left ear the volume of total photon count and AUC value of CT-left ear are larger than the combined volume of TT-left ear and IV-left ear, suggesting a synergistic effect, and those of CT-right ear are almost equal to the summation of those of IV-right group and TT-right group, suggesting no amplifying effect on the risk of systemic side effect. This study showed that CT could deliver more drugs into the inner ear, and brought a longer therapeutic window, and were more effective than intravenous or transtympanic injection alone in the pharmacokinetics.